Isolation, genome analysis and comparison of a novel parainfluenza virus 5 from a Siberian tiger (Panthera tigris) - Zhou, Niu; Chen, Liang; Wang, Chen; Lv, Mengna; Shan, Fen; Li, Wanping; Wu, Yajiang; Du, Xueqing; Fan, Jinli; Liu, Minting; Shi, Menghan; Cao, Jingjing; et al. (Frontiers in Veterinary Science, 2024)
Paramyxoviruses are important pathogens affecting various animals, including mammals and humans. Parainfluenza virus 5 (PIV5) — a member of the family Paramyxoviridae — is a major threat to the health of mammals and humans. However, studies on terrestrial wild animals infected with PIV5 are scanty. Herein, we utilized reverse transcription PCR to detect PIV5 infection in the visceral organ tissues of a Siberian tiger (Panthera tigris ssp. altaica) with vomiting, diarrhea and dyspnea before its death. A novel PIV5 (named SR strain) with a slowly progressive cytopathic effect was isolated in Vero cells and validated using a transmission electron microscope. Full-length sequencing and analysis revealed that the whole genome of the PIV5 SR strain contained 15,246 nucleotides (nt) and seven non-overlapping genes (3’-N-V/P-M-F-SH-HN-L-5’) encoding eight proteins. Phylogenetic analysis of three PIV5 strains identified in the same zoo confirmed that PIV5 strains SR and ZJQ-221 shared the closest genetic relationship as they were clustered in the same branch, while recently found Siberian tiger strain SZ2 kept a certain distance and formed a relatively unique branch. Furthermore, mutations of nt and amino acids (aa) between strains ZJQ-221, SR and SZ2 were identified. In summary, we report the identification and genomic characterization of a novel PIV5 strain SR isolated in Siberian tiger, which may help future research on interspecific transmission mechanisms.